Access [dis]Abled: Interrogating Standard Design Practices of Higher Education Writing Center Websites - Quinn, Stephanie; Belmonte, Anna; Davis, Emily; Gardewine, Andrew; Madewell, Gabrielle (Disability Studies Quarterly, 2019)
In the 11 years since the 2006 publication of the International Writing Center Association's (IWCA) Position Statements on Disability and Diversity, writing center scholars have continued to explore how disability issues intersect with writing center work including the development of accessible web content and interfaces (Hawkes, 2010). Recent studies have found that university websites were ineffectively designed, difficult to navigate, and omitting any representation or acknowledgment of students with disabilities (Gabel et al., 2016; Gabel & Miskovic, 2014; Meyer, 2008; Miskovic & Gabel, 2012). In this study, the primary author and four undergraduate student-researchers study where and how disability support is explicitly articulated on writing center websites from regional Institutions of Higher Education (IHEs) and how digital resources have been designed for students with disabilities. Results show that two out of the 35 writing center offices that exist at the 55 universities analyzed have a mission statement that explicitly articulates a support for students with disabilities. Writing center websites also ineffectively incorporate pictures, simple text, simple navigation, and other accessible features (71% of the 35 writing centers analyzed had websites where 21 – 70% of the content is inaccessible). Recommendations to address these problems are provided.